2006
DOI: 10.1021/jm051106d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Preclinical Studies of (R)-1-(4-(4-Fluoro-2-methyl-1H-indol-5-yloxy)-5- methylpyrrolo[2,1-f][1,2,4]triazin-6-yloxy)propan- 2-ol (BMS-540215), an In Vivo Active Potent VEGFR-2 Inhibitor

Abstract: A series of substituted 4-(4-fluoro-1H-indol-5-yloxy)pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of vascular endothelial growth factor receptor-2 kinase is reported. Structure-activity relationship studies revealed that a methyl group at the 5-position and a substituted alkoxy group at the 6-position of the pyrrolo[2,1-f][1,2,4]triazine core gave potent compounds. Biochemical potency, kinase selectivity, and pharmacokinetics of the series were optimized and in vitro safety liabilities were minimized to affo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(54 citation statements)
references
References 13 publications
1
53
0
Order By: Relevance
“…The exact mechanisms by which brivanib treatment induces growth inhibition are not well understood. A previous study (13) has shown that brivanib affected the host endothelium based on both in vitro and in vivo studies (vascular density, Matrigel plugs, and dynamic contrast-enhanced magnetic resonance imaging responses). It had no antiproliferative effects on L2987 lung carcinoma, HCT116 colon carcinoma, H3396 breast carcinoma, and CWR-22 prostate carcinoma cell lines in culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanisms by which brivanib treatment induces growth inhibition are not well understood. A previous study (13) has shown that brivanib affected the host endothelium based on both in vitro and in vivo studies (vascular density, Matrigel plugs, and dynamic contrast-enhanced magnetic resonance imaging responses). It had no antiproliferative effects on L2987 lung carcinoma, HCT116 colon carcinoma, H3396 breast carcinoma, and CWR-22 prostate carcinoma cell lines in culture.…”
Section: Discussionmentioning
confidence: 99%
“…BMS-540215 shows potent and selective inhibition of VEGFR and fibroblast growth factor receptor (FGFR) tyrosine kinases (13). The structures of brivanib and BMS-540215 are shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Brivanib alaninate, the orally administrated L-alanine ester prodrug, has strong antiangiogenic effects, as well as potent direct effects, on tumor cells across a range of tumor types, including liver and colon. [66][67][68][69] Sorafenib, 4-(4-(3-(4-chloro-3-(trifluoromethyl)phenyl)ureido)phenoxy)-N-methylpicolinamide 4-methylbenzenesulfonate, a kinase inhibitor of VEGFR, PDGFR, c-Kit, and Raf, has been approved for the treatment of hepatocellular carcinoma. Because brivanib targets both the FGF and VEGF signaling pathways, it may gain an advantage over sorafenib for the treatment of hepatocellular carcinoma.…”
Section: Fgfr-targetedmentioning
confidence: 99%
“…Due to the low aqueous solubility of brivanib, a prodrug strategy was pursued that resulted in a prodrug with high aqueous solubility, brivanib alaninate (13). Brivanib, the parent compound, has previously been shown to be a selective inhibitor of FGFR-1 and FGFR-2, and VEGFR-1, VEGFR-2, and VEGFR-3 in vitro (14,15). Additionally, brivanib has also shown antitumor activity in vivo against the H3396 human breast tumor xenograft model (14).…”
Section: Introductionmentioning
confidence: 99%